A Simplified Lattice Boltzmann Method for Turbulent Flow Simulation (Advances in Applied Mathematics and Mechanics, 2022)
To simulate the incompressible turbulent flows, two models, known as thesimplified and highly stable lattice Boltzmann method (SHSLBM) and large eddy simulation (LES) model, are employed in this paper. The SHSLBM was developed forsimulating incompressible viscous flows and showed great performance in numericalstability at high Reynolds numbers, which means that this model is capable of dealingwith turbulent flows by adding the turbulence model. Therefore, the LES model iscombined with SHSLBM. Inspired by the less amount of grids required for SHSLBM, alocal grid refinement method is used at relatively high Reynolds numbers to improvecomputational efficiency. Several benchmark cases are simulated and the obtainednumerical results are compared with the available results in literature, which showexcellent agreement together with greater computational performance than other algorithms.